The Nāyaka (hero) and the Nāyikā (heroine) in the Sánskrit Poetics - Rentería Alejandre, Sergio Armando (2019)
In Sanskrit poetry, extremely important aspects of poetry converge that promote human emotions and feelings from the perspective of eroticism. The prestigious Sanskrit literary tradition is basically centered on the poetic construction and the invention of stereotyped characters that promote the literary conventions of the Sanskrit lyric. The participants in these affluents of emotions and feelings embody the two characters have been described in different works on Sanskrit poetics. Hence the interest and the essential objective of these lines of research on Sanskrit poetics through the theorization and analysis made by Sanskrit theorists of both the hero and the heroine.